The Abnormal Imaging of SARS-CoV-2: A Predictive Measure of Disease Severity - Pan, Shangwen; Shu, Huaqing; Wang, Yaxin; Li, Ruiting; Zhou, Ting; Yu, Yuan; Xu, Jiqian; Xiong, Wei; Yang, Xiaobo; Zhang, Jiancheng; Yuan, Yin; Yuan, Shiying; et al. (Frontiers in Medicine, 2021)
To investigate the characteristics of SARS-CoV-2 pneumonia and evaluate whether CT，especially a certain of CT level, could be used to predict the severity of SARS-CoV-2 pneumonia. 118 patients confirmed patients had been enrolled. All data including epidemiological, clinical characteristics, laboratory results, and imagines were collected and analyzed when they were administrated first time. All patients were divided into two groups. There were 106 severe/critical patients and 12 common ones. A total of 38 female in them. The mean age was 50.5 ± 11.5 years. 80 patients had exposure history. The median time from onset of symptoms to administration was 8.0 days. The main symptoms including fever, cough, anorexia, fatigue, myalgia, headache and chilly. Lymphocytes, platelets decreased and lactate dehydrogenase increased with the increased severity (P < 0.05). Calcium and chloridion were decreased significantly in severe/critical patients than common one (P < 0.05). The mainly comorbidities were diabetes, chronic cardiovascular disease and chronic pulmonary disease, which happened in 47 patients. 69 patients had Respiratory failure, which is the most common complication, and liver dysfunction presented in 37 patients. 9 patients received mechanical ventilation therapy. 1 patient received continuous blood purification and extracorporeal membrane oxygenation (EMCO) treatments. The average stay was 18.1±10.8 days. 4 patients died. The median of the radiographic score was 4 in common, 5 in severe/critical illness, which was a significant difference between the two groups. The radiographic score was negative correlation with OI (ρ = -0.467, P < 0.01). The OI in severe/critical ill cases decreased significantly with the disease getting worse, which was related to the lesion area in left lung and right lung (ρ = 0.688, R = 0.733). OI, the lesion area in left lung and right lung, lymphocytes, etc. were associated with different degrees of SARS-CoV-2 pneumonia (P＜0.05). The lesion area in left lung and right lung were the possible predictive factors for the severe/critical ones. Patients with SARS-CoV-2 pneumonia have obvious clinical manifestations and laboratory changes. Combing clinical features and quantitative the lesion area in fourth level of CT could effectively predict severe/critical types.